Effect of Feeding Moringa oleifera Replacing TMR on Nutrients Intake, Rumen Fermentation and Economics in Adult Cattle - Chaudhary, M. N.; Shekh, M. A.; Devalia, B. R.; Darji , V. B.; Sherasiya, A. N. (International Journal of Bio-resource and Stress Management, 2023)
A study was undertaken at Animal Nutrition Research Station, College of Veterinary Science & Animal Husbandry, Anand Agricultural University, Anand, Gujarat, India during January–March, 2020 to determine effect of feeding Moringa oleifera on nutrient intake, rumen fermentation and economics in adult cattle. Fourteen adult cattle were randomly divided into two groups on the basis of body weight viz., T1 (control): TMR (Wheat straw-70% and Concentrate-30%) and T2 (Treatment): Control TMR+Green Moringa oleifera (replacing TMR with 20% of total protein requirement of animal from green Moringa oleifera). The daily dry matter intake (kg), crude protein intake (g), digestible crude protein intake (g), TDN intake (kg) was found non-significant in both the groups, whereas dry matter intake and TDN intake (kg 100 kg- BW and g kg-1 W0.75) were significantly higher in control group. The crude protein intake (g 100 kg-1 BW) and DCP intake (g 100 kg-1 BW and g kg-1 W0.75) were significantly higher in Moringa supplemented group. The average ruminal pH, ammonical nitrogen (NH3-N) (mg dl-1), Non-protein nitrogen (NPN) (mg dl-1), soluble nitrogen (mg dl-1) and TCA precipitable nitrogen (mg dl-1) were found non-significant. However, the concentration of TVFA (mM dl-1) and total nitrogen (mg dl-1) were significantly higher in Moringa supplemented group. The daily feed cost was reduced by 8.93% in Moringa oleifera supplemented group but statistically the difference was found non-significant.